Investigating your career - Jordan, Ann K; Whaley, Lynne T (Australia : Thomson, 2004)
By emphasizing why lifelong learning is an essential skill for career planning, Investigating Your Career helps students in grades 7 and 8 make the most of their future high school years. This semester-length middle school text encourages students to investigate their own identity and implement career plans that fit their individuality by matching career focus to their interests, abilities, values, personalities and personal goals. The importance of volunteer work and extra-curricular activities is explored as well as educational and work experiences that will help build the skills needed to be successful in a chosen career.
includes index.
Keywords: Career development; Vocational guidance